2022
DOI: 10.4314/ahs.v22i3.43
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum lipid profile, body mass index and osteoporosis in postmenopausal Sudanese women

Abstract: Background: Epidemiological observations suggest links between osteoporosis and the risk of acute cardiovascular events. Whether the two clinical conditions are linked by common pathogenic factors or atherosclerosis per se remains incompletely understood. The reduction of bone density and osteoporosis in postmenopausal women contributes to elevated lipid parameters and body mass index (BMI). Objective: To investigate the relationship between serum lipid profile, BMI and osteoporosis in postmenopausal wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The mechanism of this relation may be directly related with the cholesterol biosynthetic pathway, which determines cholesterol levels and contributes to the activity of the osteoclast. Beneficial effect of lipid reducing drugs such as statins on BMD has been seen in most previous studies [ 14 ]. In our study results demonstrated that the higher total cholesterol and LDL cholesterol levels were observed in the osteoporosis group compared to the oseopenia group.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of this relation may be directly related with the cholesterol biosynthetic pathway, which determines cholesterol levels and contributes to the activity of the osteoclast. Beneficial effect of lipid reducing drugs such as statins on BMD has been seen in most previous studies [ 14 ]. In our study results demonstrated that the higher total cholesterol and LDL cholesterol levels were observed in the osteoporosis group compared to the oseopenia group.…”
Section: Resultsmentioning
confidence: 99%